Anti-integrin treatment as an effective alternative for a patient with ulcerative colitis - Biegańska, Ewa; Rokicki, Karol; Karolewska-Bochenek, Katarzyna; Łazowska-Przeorek, Izabella; Banasiuk, Marcin (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Paediatric ulcerative colitis (UC) has a tendency to run in an extensive manner, with frequent exacerbations. As a result, treatment of paediatric patients is a complex process demanding thorough evaluation, careful monitoring, and selection of appropriate medication. We present a case report of UC in an 11-year-old boy diagnosed at the age of 7 years. During 3 years of treatment many therapeutic methods were used, but none brought a long-lasting therapeutic effect. Due to exhaustion of available therapeutic options, off-label treatment with vedolizumab was introduced. Currently, in his 15th month of the therapy, the patient remains in remission. This case, in line with the available literature, indicates that there might be a need to include vedolizumab to the UC standard treatment regimens. Moreover, it should also be considered for inclusion in funding programs of national health insurance companies. It is of a crucial importance for patients because in some cases it remains the last treatment option.